Severe congenital chorioretinitis caused by congenital lymphocytic choriomeningitis virus infection - Ansari, Nadia (Am J Ophthalmol Case Rep, 2021)
PURPOSE: To describe a case of congenital lymphocytic choriomeningitis virus (LCMV), a potentially severe and under-diagnosed etiology of congenital chorioretinitis. OBSERVATIONS: A 5-month old boy presented with esotropia. Examination revealed light perception vision in the right eye and normal fixation and following behavior in the left eye, and a 50PD esotropia with full versions. The external, anterior segment, and pupil exams were normal. Fundus examination demonstrated slightly pale optic nerves, numerous geographic atrophic and hyperpigmented lesions along the vascular arcades in both eyes that extended into the fovea of the right eye. Head computed tomography (CT) imaging demonstrated bilateral cerebral volume loss with consequential ex vacuo dilation of the lateral ventricles and scattered intracranial calcifications. Serum IgG and IgM titers for toxoplasmosis, rubella, cytomegalovirus (CMV), herpes simplex virus (HSV), syphilis, and zika were all negative. Upon communication of negative TORCHS titers, the mother recalled a severe rat infestation of their home during the pregnancy. A LCMV antibody titer was then ordered and which resulted positive for IgG antibodies. CONCLUSIONS AND IMPORTANCE: Congenital LCMV infection is an under-recognized cause of congenital chorioretinitis.